2010
DOI: 10.1111/j.1471-4159.2010.06881.x
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐6‐type cytokines in neuroprotection and neuromodulation: oncostatin M, but not leukemia inhibitory factor, requires neuronal adenosine A1 receptor function

Abstract: J. Neurochem. (2010) 114, 1667–1677. Abstract Neuroprotection is one of the prominent functions of the interleukin (IL)‐6‐type cytokine family, for which the underlying mechanism(s) are not fully understood. We have previously shown that neuroprotection and neuromodulation mediated by IL‐6 require neuronal adenosine A1 receptor (A1R) function. We now have investigated whether two other IL‐6‐type cytokines [oncostatin M (OSM) and leukemia inhibitory factor (LIF)] use a similar mechanism. It is presented here th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 43 publications
3
36
0
Order By: Relevance
“…In addition, its role in modulation of cell metabolism (Cunha, 2001), neuron-glia communication (Boison et al, 2010), and the tuning of growth factor signaling (Gomes et al, 2011) is becoming evident. Indeed, we and others have recently shown that the chemokine CX 3 CL1 and the cytokines IL-6 and OSM are able to drive neuroprotection only in the presence of functional A 1 R (Biber et al, 2008;Lauro et al, 2008Lauro et al, , 2010Moidunny et al, 2010;Cipriani et al, 2011). In particular, IL-6 and OSM potentiate the expression and the function of neuronal A 1 R and therefore the ADO effects on neurotransmission and neuroprotection (Moidunny et al, 2010); on the other hand, CX 3 CL1 neuroprotection is due to ADO release from microglia, activation of A 1 R, and, possibly, the subsequent release of glial-soluble factors that contribute to neuroprotection (Lauro et al, 2010).…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…In addition, its role in modulation of cell metabolism (Cunha, 2001), neuron-glia communication (Boison et al, 2010), and the tuning of growth factor signaling (Gomes et al, 2011) is becoming evident. Indeed, we and others have recently shown that the chemokine CX 3 CL1 and the cytokines IL-6 and OSM are able to drive neuroprotection only in the presence of functional A 1 R (Biber et al, 2008;Lauro et al, 2008Lauro et al, , 2010Moidunny et al, 2010;Cipriani et al, 2011). In particular, IL-6 and OSM potentiate the expression and the function of neuronal A 1 R and therefore the ADO effects on neurotransmission and neuroprotection (Moidunny et al, 2010); on the other hand, CX 3 CL1 neuroprotection is due to ADO release from microglia, activation of A 1 R, and, possibly, the subsequent release of glial-soluble factors that contribute to neuroprotection (Lauro et al, 2010).…”
Section: Discussionmentioning
confidence: 92%
“…Indeed, we and others have recently shown that the chemokine CX 3 CL1 and the cytokines IL-6 and OSM are able to drive neuroprotection only in the presence of functional A 1 R (Biber et al, 2008;Lauro et al, 2008Lauro et al, , 2010Moidunny et al, 2010;Cipriani et al, 2011). In particular, IL-6 and OSM potentiate the expression and the function of neuronal A 1 R and therefore the ADO effects on neurotransmission and neuroprotection (Moidunny et al, 2010); on the other hand, CX 3 CL1 neuroprotection is due to ADO release from microglia, activation of A 1 R, and, possibly, the subsequent release of glial-soluble factors that contribute to neuroprotection (Lauro et al, 2010). In contrast, in the present work we found that CXCL16 exerts neuroprotection against Glu insult only in the presence of functional A 3 R, the inactivation of all of the other ARs being unable to limit the CXCL16 effect.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Ablation of OSM gene in mouse results in a significant loss of a subset of nociceptive neurons in the dorsal root ganglia (DRG) and defects in pain sensitivity [16]. In addition, OSM is shown to protect neurons from excitotoxic injury in vitro and in vivo [19], [20]. We found recently that OSM protects both rod and cone photoreceptors, and promotes regeneration of cone outer segments in a transgenic rat model of retinal degeneration [21].…”
Section: Introductionmentioning
confidence: 99%